Spinal anesthesia: an evergreen technique - Di Cianni, S.; Rossi, M.; Casati, et al., A. (Acta Biomedica Atenei Parmensis, 2008)
Spinal anesthesia is a simple technique that provides a deep and fast surgical block through the injection of small doses of local anesthetic solution into the subarachnoid space. The purpose of this review is to provide an overview on recent developments on local anesthetic drugs, side effects, and special techniques of intrathecal anesthesia. Spinal anesthesia can be considered adequately safe, and severe complications are reasonably rare. The cardiovascular effects associated with sympathetic block are more frequent, but successfully treated with volume expansion and administration of vasoactive drugs. It is clear that the total dose of local anesthetic injected into the subarachnoid space is the most important determinant of both therapeutic and unwanted effects of spinal anesthesia. Several studies have also demonstrated the efficacy and safety of using small doses of long acting agents, such as bupivacaine or ropivacaine, to produce an adequately short spinal block in outpatients. Levopivacaine, the pure S(-)-enantiomer of racemic bupivacaine showed a lower risk of cardiovascular and central nervous system (CNS) toxicity than bupivacaine. In the last years we have assisted important changes in the health care organization, with most of the surgical procedures performed on outpatients or on elderly patients with concomitant diseases. This forced us to change the indications and clinical use of intrathecal anesthesia techniques, which have been modified according to the changing needs of surgery. The development of new drugs and special techniques for spinal anesthesia will further improve the clinical use of this old but evergreen technique.